2021
DOI: 10.1177/13540688211008842
|View full text |Cite
|
Sign up to set email alerts
|

Informal institutions and gendered candidate selection in Brazilian parties

Abstract: Six electoral cycles since the implementation of Brazil’s gender quota, just 15% of the 513 members of the Chamber of Deputies are women. We ask how parties’ use of informal institutions mediates the effectiveness of the gender quota. Drawing on data from more than 4,000 state-level party organizations, we show that parties employ informal practices that intentionally and non-intentionally interact with gender equity rules to affect women’s political representation: the intentional nomination of phantom candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Recent evidence has shown that resources matter for electoral outcomes (Arraes, Amorim & Simonassi, 2017;Borba & Cervi, 2017;Jacobson, 1978;Samuels, 2001b). Candidates with political capital benefit, perpetuating the inequality of political representation (especially for racial minorities and women) (Bolognesi et al, 2020;Gatto & Wylie, 2022). Donors benefit after campaign contributions (Mancuso, 2015;Santos et al, 2015).…”
Section: Frameworkmentioning
confidence: 99%
“…Recent evidence has shown that resources matter for electoral outcomes (Arraes, Amorim & Simonassi, 2017;Borba & Cervi, 2017;Jacobson, 1978;Samuels, 2001b). Candidates with political capital benefit, perpetuating the inequality of political representation (especially for racial minorities and women) (Bolognesi et al, 2020;Gatto & Wylie, 2022). Donors benefit after campaign contributions (Mancuso, 2015;Santos et al, 2015).…”
Section: Frameworkmentioning
confidence: 99%
“…One important strand of literature has studied the gendered effects of these informal rules and reveals how parties intentionally and unintentionally employ informal practices that affect the outcome of candidate selection and explain the underrepresentation of women in parliament (e.g. Kenny and Verge, 2016; Colley and Van Acker, 2020; Gatto and Wylie, 2022). Another strand of research examines the interaction between informal and formal rules showing that informal rules are not always congruent with the formal rules in place, but are sometimes supplementary and rather interact or even compete with them (Cross, 2018; Kelbel, 2020; Meserve et al, 2017; Vandeleene and Van Haute, 2021).…”
Section: Theoretical Framework: Informal Rules and Competing Logics O...mentioning
confidence: 99%
“…The Brazilian case presents an opportunity to investigate the implications of coalitional presidentialism for women's cabinet appointments. First, unlike many countries in the world where the adoption of quotas has transformed the gendered composition of legislatures and party leadership (Hughes et al, 2019; Schwindt-Bayer, 2009), women's legislative representation has remained largely constant over time even after the national implementation of the quota law in 1998 and subsequent efforts to strengthen the quota (Gatto and Wylie, 2021; Santos, 2021; Wylie et al, 2019). This provides a stable context to isolate the effects of coalitional presidentialism – and not other changes in the wider dynamics of women's political representation – on women's ministerial presence.…”
Section: Coalitional Presidentialism and Women's Political Representa...mentioning
confidence: 99%